Intralesional steroid injection in keloid ear — a prospective observational study - Vinod Bangalore Narayanaswamy; Tejaswini H; Saritha H M; Udayabhanu H N; Nagarathna H K (The Egyptian Journal of Otolaryngology)
Abstract Background Keloid is a fibro-proliferative dermal benign growth affecting the Asian population. In India, ear keloids are common, often resulting from ear piercing, a prevalent cultural practice. The resultant ear keloids pose aesthetic concerns, leading to significant psychological distress, and necessitating effective treatment. While various treatment options are available, their outcomes and recurrence rates vary, highlighting the need for individualized and optimal management strategies. Our study aimed to observe the combined effect of intralesional triamcinolone with hyaluronidase on keloid regression. Methods This prospective observational study was conducted at our tertiary care institute over 1 and a half years. Fifty patients who met the inclusion criteria were enrolled and received intralesional triamcinolone injection with hyaluronidase. Keloid regression was assessed using the Vancouver Scar Scale (VSS), while the visual analogue score (VAS) and patient satisfaction score (PSS) provided subjective evaluations of symptom relief. All patients underwent compression therapy. Patients were evaluated at every visit and then at 1 year for symptom relief, keloid regression, and complications if any. Results Demographic data of all patients were recorded. Ear keloids were predominantly observed in females, with a male-to-female ratio of 18:32. The most common etiology was trauma following ear piercing, accounting for 46% of cases. All patients showed improvement in VSS, VAS, and PSS scores in the follow-up visits. A total of 98% of patients demonstrated a complete treatment response, with only a single instance of recurrence. Conclusion Intralesional triamcinolone with hyaluronidase provides satisfactory symptomatic relief and has lower recurrence rates. All patients showed improvement in the Vancouver Scar Scale and had enhanced VAS and PSS scores.